Normal butanol fraction of Polygonum hydropiper L. flavonoids reduces inflammation caused by PCV2 infections in cell and mouse models - Wei, Yu-heng; Zhou, Shu-mian; Zhao, Wen; Chen, Qi; Wang, Qiu-hua; Yu, Mei-ling; Wei, Ying-yi; Hu, Ting-jun (Frontiers in Veterinary Science, 2025)
IntroductionThe normal butanol fraction of Polygonum hydropiper L. flavonoids (FNB) exhibits significant anti-inflammatory effects. This study investigated FNB's impact on inflammatory responses induced by Porcine circovirus type 2 (PCV2) in cell and mouse models.MethodsAn inflammatory model was established in RAW264.7 cells infected with varying PCV2 concentrations. And assigning both RAW264.7 cells and 108 SPF-grade KM mice to Control, PCV2, Rutin, and various dosages of FNB groups. Inflammatory factors such as Monocyte Chemoattractant Protein-1 (MCP-1), interleukin-6 (IL-6), IL-8, IL-10, Tumor Necrosis Factor-alpha (TNF-α), Reactive Oxygen Species (ROS), and Nitric Oxide (NO) were quantified using ELISA, RT-qPCR and immunohistochemistry.ResultsResults showed that a PCV2 titer of 104.5 TCID50/0.1 mL when applied to RAW264.7 cells effectively established an in vitro inflammatory model at 12 and 24 h post-infection. Following PCV2 infection, all the inflammatory factors displayed a significant increased both in culture supernatant and intracellular mRNA expression levels (p < 0.05 or p < 0.01), but these levels were reduced by FNB treatment (p < 0.05 or p < 0.01). In mouse sera post-PCV2 infection also showed elevated levels of IL-6, IL-8 IL-10, TNF-α, and MCP-1 (p < 0.05 or p < 0.01). Additionally, mRNA and protein levels for TNF-α, IL-8, IL-10, IL-6, and iNOS rose significantly in lung tissues (p < 0.01) but decreased with FNB treatment (p < 0.05 or p < 0.01).DiscussionThese findings suggest that FNB reduces inflammatory factor production and modulates the inflammatory response triggered by PCV2 infection, potentially enhancing host resistance against it.